SUPERVISION MODERATING INTERNATIONAL SAFETY MANAGEMENT CODE (ISM CODE) AND CULTURAL ORGANIZATION THE PERFORMANCE OF EMPLOYEES - chrystanto, andri; Khuzaini, Khuzaini; Suwitho, Suwitho (Jurnal Aplikasi Manajemen, 2019)
The safety of a cruise is a big responsibility and is the most important thing in all aspects. Shipping transportation safety is very close to the human resources that operate the ship. Thus, the performance of employees is very important in supporting the safety and quality of shipping in accordance with the regulations. The ISM Code is an international standard of safety management in the operation of ships as well as efforts to prevent or control environmental pollution. This study aims to analyze and examine the effect of the ISM Code, and organizational culture on employee performance with supervision as a moderating variable. The population in this study included long-distance crossing officers working at PT Dharma Lautan Utama. In this study, sampling was based on purposive sampling criteria, then a sample of 72 respondents was obtained. Data collection techniques in this study used a questionnaire. The type of data used in this study is primary data collected by sending questionnaires to respondents. The research method is quantitative, while the data analysis technique uses the Moderating Regression Analysis (MRA). The results of this study indicate that the ISM Code, and organizational culture have a positive influence, while supervision variables as moderating factors can strengthen the influence of the International Safety Management Code (ISM Code), and organizational culture on employee performance.